1975
DOI: 10.1254/jjp.25.453
|View full text |Cite
|
Sign up to set email alerts
|

Physical Dependence on Morphine, Phenobarbital and Diazepam in Rats by Drug-Admixed Food Ingestion

Abstract: Abstract-To produce physical dependence on morphine, phenobarbital and diazepam in rats, these drugs were mixed with the powder form of rat food in concentrations of 0.5 mg/g, 1 mg/g and 2 mg/g of food. One group of rats (the lower dose group) was continuously exposed for I week to two morphine-admixed foods with morphine to food ratios of 0.5 mg/g and 1 mg/g in a cage. The other group (the higher dose group) could choose between two morphine-admixed foods with morphine to food ratios of 1 mg/g and 2 mg/g. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Other studies extended this finding to demonstrate that physical dependence on barbiturates can be demonstrated in rodents (9,(11)(12)(13)(14). Until recently, severe physical dependence on pentobarbital as manifested by withdrawal convulsions had not been shown in rodents.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies extended this finding to demonstrate that physical dependence on barbiturates can be demonstrated in rodents (9,(11)(12)(13)(14). Until recently, severe physical dependence on pentobarbital as manifested by withdrawal convulsions had not been shown in rodents.…”
mentioning
confidence: 90%
“…For preparing the drug admixed food, sodium pentobarbital (Tokyo kasei Kogyo, Tokyo, Japan) was mixed with a normal powdered food (CA-1, Japan Clea, Tokyo, Japan) in a mortar (13,14). Each rat was allowed to eat the pentobarbital admixed food and to drink tap water ad libitum.…”
mentioning
confidence: 99%
“…Furthermore, the rats on repeated adminis tration of pentazocine-admixed food were challenged with levallorphan, but no distinct withdrawal signs were precipitated in these animals compared with those on morphine, codeine, or pethidine treatment (14,15). Keats and Telford (22) reported that neither levallorphan nor nalorphine exerted any antagonistic action on the respiratory de pression with pentazocine.…”
Section: Methodsmentioning
confidence: 99%
“…A Drug-Admixed Food (DAF) method developed by the authors (14) was used in the present study. This method is easy to follow and not time-consuming, and as described in a previous paper of a study on the physical dependence on pethidine (15), this method has been proven to be applicable to a dependence formation study on drugs rapidly metabolized or those which become quickly toxic as in the case of barbiturates when continuously applied (16).…”
mentioning
confidence: 99%
“…The drug admixed food (DAF) method developed by Yanaura et al (10,11) is an easy way to produce physical dependence on opioids in rodents without the stress of surgery or injection. It is well-known that the degree and severity of physical dependence are influenced by dose, frequency (dosing inter val) and duration of drug administration and that the frequency is the most important factor (12).…”
Section: Physical Dependence 1 Opioidmentioning
confidence: 99%